PENGARUH BRAND IMAGE DAN BAURAN PEMASARAN TERHADAP MINAT BELI DAN KEPUTUSAN PEMBELIAN PADA ES KRIM WALL’S DI PEKANBARU - Setiawan, Budi; Sulistyowati, Lilis; Restuti, Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to analyze the influence of brand image and marketing mix to buying interest and purchase decisions on the Wall's ice cream in the city of Pekanbaru. This study used 102 samples. The analytical method used is descriptive analysis method is a way to test variables, regression test, and the last test path analysis or path analysis. From the results of testing that has been done, the magnitude of the coefficient of the variable influence of X1 (Brand Image) to variable Y2 (purchase decision) obtained for 0,102. While the t value at 4,208> 1,984 t table. While the magnitude of the coefficient of the variable influence of X2 (Marketing Mix) to variable Y2 (Purchasing Decisions) obtained for 0,124. While the t value of 3.233> t table 1984. Indirect relationship variables Brand Image and Marketing Mix to the purchase decision variable through variable interest in buying the Wall's ice cream Pekanbaru is greater than the result of a direct relationship variables Brand Image and Marketing Mix to the purchase decision variable through variable interest in buying the Wall's ice cream Pekanbaru. The magnitude of the coefficient of the variable influence of Y1 (Interests Purchase) to variable Y2 (Purchasing Decisions) obtained for 0,502. While the t value of 2.667> t table 1.984.Keywords: Brand Image, Marketing Mix, Interests Purchase, Purchase Decision